Sharia, Two Sides of the Same Coin: The Contradictions between Sharia and Adat (Case Studies of Minangkabau’s Matrilineal and Land Tenure System) - Wanto, Adri (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
Since the implementation of regional autonomy laws in Indonesia, large numbers of sharia-inspired laws have been implemented in the West Sumatera Province. Furthermore, some Minangkabau people, the ethnic group indigenous to the province, have insisted in the abolishment of the matrilineal and land tenure system, which they believe is not in accordance with sharia. For hundreds of years, the Minangkabau ethnic have been famous for being one of the world’s largest matrilineal societies, and the inheritance of land and property ownership is handed down according to the matrilineal principle over generations. As a result, conflicts arise within indigenous communities (internal conflict-horizontal) since its proponents and opponents are equally strong in the society. The most interesting aspect to be analyzed is the fact that the disputing groups use sharia to legitimise their points of view. Some argue that the matrilineal and land tenure system is in accordance with sharia while the others argue otherwise. This study will focus on the discourse beyond the epistemic claim made by the disputing groups. This paper argues that the mix of ideological, political and economic interests play a significant role behind the struggle for control of the religious discourse, particularly related to the matrilineal and the land tenure system in the Minangkabau post reformasi era.Sejak pelaksanaan undang-undang otonomi daerah di Indonesia, banyak terbentuk undang-undang yang terinspirasi dari hukum syariah dan telah diterapkan di wilayah Provinsi Sumatera Barat. Terlebih, beberapa kelompok masyarakat Minangkabau sebagai etnis asli provinsi tersebut, bersikeras dalam hal penghapusan budaya matrilineal dan sistem kepemilikan tanah, yang mereka percaya tidak sesuai dengan syariah. Selama ratusan tahun, etnis Minangkabau terkenal sebagai salah satu masyarakat matrilineal terbesar di dunia, demikian pula pemberian warisan tanah dan kepemilikan lahan atau bangunan diturunkan sesuai dengan prinsip matrilineal tersebut. Sebagai akibatnya timbul konflik dua kubu dalam masyarakat adat yang sama kuat. Aspek yang paling menarik untuk dianalisis adalah kenyataan bahwa kelompok yang bersengketa itu menggunakan syariah untuk melegitimasi pandang mereka masing-masing. Sebagian kelompok berpendapat bahwa sistem kepemilikan matrilineal dan tanah adalah sesuai dengan syariah sementara yang lain berpendapat sebaliknya. Studi ini akan fokus pada wacana klaim epistemologis yang dibuat oleh kelompok-kelompok yang bersengketa. Tulisan ini berpendapat bahwa campuran kepentingan ideologi politik dan ekonomi memiliiki peran penting di balik perjuangan untuk mengendalikan wacana keagamaan, terutama berkaitan dengan matrilineal dan sistem kepemilikan tanah di Minangkabau pada era pasca reformasi.